Mechanical testing of solid polymers - Gopez, Adolfo Jesus R.
Standard tests for polymer mechanical properties are designed for use with easily available or easily constructed apparatus to allow widespread use of such tests. Properties measured are often used for design purposes and these properties are threshold or extremal values. No real effort is made to compare materials at intermediate testing stages. Non-standard tests such as the tensile test at constant true strain rate and the plane simple shear test are therefore used to explore the plastic deformation behavior of solid polymers. Strain rate and temperature effects have been explored to establish constitutive equations of flow for some polymers while the mechanism of plastic deformation in glassy polymers has been explored. A comparison between amorphous and semi-crystal-line polymers from the point of view of mechanical properties is made. Some aspects of plastic instability in polymers are also discussed.